2011
DOI: 10.1007/s10811-011-9759-z
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of a Scenedesmus acutus strain to be used for bioremediation of urban wastewater

Abstract: Green microalgae, due to their short growth cycle and to their ability to photosynthetically fix carbon dioxide producing an oil-rich biomass, have been proposed as an attractive alternative feedstock for the production of "second generation" biofuels. However, it has been anticipated that owing to their ability to colonize very different environments characterized by high levels of nitrogen, they can also be good candidates for bioremediation, thus integrating environmental protection with sustainable biomass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(19 citation statements)
references
References 34 publications
2
16
0
1
Order By: Relevance
“…This lipid content was much higher than most of the records in the outdoor cultures, indicating a lipid content of 15.6% for Botryococcus braunii (Bazaes et al, 2012), 19-32% for Chlorella sp (Moheimani, 2012(Moheimani, , 2013, 34.7% for N. oculata and N. salina (Quinn et al, 2012), less than 30% for S. acutus (Doria et al, 2011), and 24-30% for Tetraselmis suecica (Moheimani, 2013). In addition, the lipid productivity averaged at 28.1 mg…”
Section: Abundansmentioning
confidence: 74%
“…This lipid content was much higher than most of the records in the outdoor cultures, indicating a lipid content of 15.6% for Botryococcus braunii (Bazaes et al, 2012), 19-32% for Chlorella sp (Moheimani, 2012(Moheimani, , 2013, 34.7% for N. oculata and N. salina (Quinn et al, 2012), less than 30% for S. acutus (Doria et al, 2011), and 24-30% for Tetraselmis suecica (Moheimani, 2013). In addition, the lipid productivity averaged at 28.1 mg…”
Section: Abundansmentioning
confidence: 74%
“…Proulx et al 1993;Chevalier et al 2000;Doria et al 2012). For this purposes, the microalgae can be cultivated in suspension or attached to a firm surface.…”
Section: The Algae and Their Role In Biotechnologymentioning
confidence: 99%
“…were tested to develop technology suitable for the cool climate in Canada (Talbot and de la Noüe 1993; Chevalier et al 2000). Doria et al (2012) isolated the microalga Scenedesmus acutus from municipal wastewater and recorded its biomass production coupled with reduction in nutrients during growth in a tubular bioreactor (50 l). She reports a biomass production of 0.24 g DW l −1 d −1 and complete removal of N from wastewater.…”
Section: Laboratory-scale Studies Using Suspension Culturesmentioning
confidence: 99%
“…The pH in all the photobioreactors increased to about 7.0-8.0, which was a positive factor considering that vinasse pH was 4.0. Doria et al (2012) and Oliveira (2013) demonstrated the growth of microalgae using wastewater. The results of Oliveira (2013) were similar to those obtained in this study, which obtained a production of 0.48 g/L in cultures with 28% of vinasse.…”
Section: Ccd Studiesmentioning
confidence: 99%
“…They can also be used to treat the industrial effluents and sewage. Doria et al (2012) used Scenedesmus acutus inoculated in wastewater from anaerobic digestion process that resulted in a production of 0.74 g/L of biomass in eight days. Oliveira (2013) observed that Scenedesmus sp could be used to treat up to 30% of domestic effluents (vinasse has similar characteristics) and obtained a biomass production of 0.48 g/L in ten days.…”
Section: Introductionmentioning
confidence: 99%